2017
DOI: 10.4103/ijo.ijo_509_17
|View full text |Cite
|
Sign up to set email alerts
|

A literature review and update on the incidence and microbiology spectrum of postcataract surgery endophthalmitis over past two decades in India

Abstract: Purpose:The purpose of this study was to review the incidence and microbiology of acute postcataract surgery endophthalmitis in India.Methods:Systematic review of English-language PubMed referenced articles on endophthalmitis in India published in the past 21 years (January 1992–December 2012), and retrospective chart review of 2 major eye care facilities in India in the past 5 years (January 2010–December 2014) were done. The incidence data were collected from articles that described “in-house” endophthalmiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…recent review reported that endophthalmitis rates in India have ranged between 0.04%–0.15% during the past two decades. [ 13 ] This is in line with other reported rates internationally,[ 6 15 16 17 ] but based on the extremely high-volume of cataract surgery performed in India, Lalitha et al . estimated that there may be as many as 4800 Indian endophthalmitis cases annually.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…recent review reported that endophthalmitis rates in India have ranged between 0.04%–0.15% during the past two decades. [ 13 ] This is in line with other reported rates internationally,[ 6 15 16 17 ] but based on the extremely high-volume of cataract surgery performed in India, Lalitha et al . estimated that there may be as many as 4800 Indian endophthalmitis cases annually.…”
Section: Discussionsupporting
confidence: 87%
“…There are currently more than 15,000 active cataract surgeons in India who perform approximately 6 million cataract surgeries annually. [ 13 ] In contrast to the West, manual small incision extracapsular cataract surgery (MSICS) accounts for a higher percentage of procedures in India due to a greater prevalence of indigent patients. Another important difference in India is the commercial availability of single-use IC moxifloxacin formulations (Auromox, Aurolab, India and 4-Quin, Entod pharmaceuticals, India).…”
mentioning
confidence: 99%
“…Postoperative fungal infections of the eye have been reported to present as endogenous endophthalmitis with an incidence ranging from 16.7% to 70% [1][2]. Endogenous endophthalmitis occurs especially in patients with drug-induced immunosuppression, organ transplantation, or a nidus for infection such as an indwelling catheter.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 7 8 ] Cluster endophthalmitis cases are generally exogenous in origin and are described in association with various solutions/fluids used during surgery such as internal fluid pathways of phacoemulsifier, irrigating solutions, viscoelastic substances, intracameral injections, and with drops/drug solutions used in perioperative period. [ 9 10 11 ] They can also occur due to breach in the sterilization or aseptic protocols. Loss of sight in one eye has a profound impact on the patient's life, their social well-being, and possibly their profession.…”
mentioning
confidence: 99%